Family Support Among Stroke Patients Hospitalized at Dr. Drs. M. Hatta Brain Hospital, Bukittinggi, in 2025 - Anisa Fetriani; Reni Chaidir; Ade Sry Wahyuni (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
Stroke is one of the main causes of disability and death in the world, including in Indonesia. Stroke ranks second as a non-communicable disease causing death and stroke is also the third leading cause of disability worldwide. Stroke patients often experience significant physical, psychological and social changes, requiring intensive support from the family to facilitate the recovery process. This study aims to determine the description of family support for stroke in inpatient care at DR Brain Hospital. Drs. M. Hatta Bukittinggi 2025. This type of research is analytical descriptive. The research sample consisted of 96 families of hospitalized stroke patients who were selected using a purposive sampling technique. Data was collected using a questionnaire that measured aspects of informational, emotional, instrumental and reward support. From the results of research conducted on 96 patient families, it was possible to obtain a frequency distribution of descriptions of family support for stroke patients in the inpatient setting at Dr. Brain Hospital. Drs. M. Hatta Bukittinggi in 2025 shows that family support is mostly in the adequate family support category, 58 people (60.4%), 27 people (28.1%) have good family support and 11 people (11.5%) have insufficient family support. The conclusion of this study is that most of the families of stroke patients at Dr. Brain Hospital. Drs. M. Hatta Bukittinggi provided sufficient support.